Dental age estimation of growing children by measurement of open apices: A Malaysian formula - Cugati, Navaneetha (J Forensic Dent Sci, 2015)
BACKGROUND: Age estimation is of prime importance in forensic science and clinical dentistry. Age estimation based on teeth development is one reliable approach. Many radiographic methods are proposed on the Western population for estimating dental age, and a similar assessment was found to be inadequate in Malaysian population. Hence, this study aims at formulating a regression model for dental age estimation in Malaysian children population using Cameriere's method. MATERIALS AND METHODS: Orthopantomographs of 421 Malaysian children aged between 5 and 16 years involving all the three ethnic origins were digitalized and analyzed using Cameriere's method of age estimation. The subjects’ age was modeled as a function of the morphological variables, gender (g), ethnicity, sum of normalized open apices (s), number of tooth with completed root formation (N(0)) and the first-order interaction between s and N(0). RESULTS: The variables that contributed significantly to the fit were included in the regression model, yielding the following formula: Age = 11.368-0.345g + 0.553N(o) -1.096s - 0.380s.N(o), where g is a variable, 1 for males and 2 for females. The equation explained 87.1% of total deviance. CONCLUSION: The results obtained insist on reframing the original Cameriere's formula to suit the population of the nation specifically. Further studies are to be conducted to evaluate the applicability of this formula on a larger sample size.